Professional guide to diseases - Willis, Laura M., 1969- (Wolters Kluwer, 2020)
"Get ready to provide efficient, informed patient care, with the newly updated Professional Guide to Diseases , 11th Edition . This comprehensive guide offers the causes, signs and symptoms for more than 600 disorders, with expert nursing direction on tests, assessments, diagnosis, treatments, and special considerations. Whether you are a student preparing for board certification or are a new or experienced nurse, this is vital support for understanding correct treatment of the common conditions seen almost daily" -- Amazon.com.